Book Review: Romila Thapar, The Past as Present: Forging Contemporary Identities through History. (January 2016) - Roy, Ratan Kumar
Romila Thapar, The Past as Present: Forging Contemporary Identities through History, 2014, New Delhi: Aleph Book Company, pp. 329, ₹ 595, ISBN: 978-93-83064-01-4.